2022
DOI: 10.1038/s41422-022-00672-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical mechanism for increased infectivity and immune evasion of Omicron BA.2 variant compared to BA.1 and their possible mouse origins

Abstract: The Omicron BA.2 variant has become a dominant infective strain worldwide. Receptor binding studies show that the Omicron BA.2 spike trimer exhibits 11-fold and 2-fold higher potency in binding to human ACE2 than the spike trimer from the wildtype (WT) and Omicron BA.1 strains. The structure of the BA.2 spike trimer complexed with human ACE2 reveals that all three receptor-binding domains (RBDs) in the spike trimer are in open conformation, ready for ACE2 binding, thus providing a basis for the increased infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 46 publications
6
83
1
3
Order By: Relevance
“…Alternatively, it was shown that the Wuhan strain binds with a good specificity to cat ACE2, but not to mouse ACE2. Considering the fact that the Omicron strain efficiently binds both the murine and the human ACE2-receptors, the possible evolution pathway could be the following: human–cat–mouse–human [ 21 ]. Thus, an inter-species evolutionary trajectory for the Omicron outbreak is possible [ 20 , 21 ].…”
Section: Mutation Dynamic Is Associated With Omicron Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it was shown that the Wuhan strain binds with a good specificity to cat ACE2, but not to mouse ACE2. Considering the fact that the Omicron strain efficiently binds both the murine and the human ACE2-receptors, the possible evolution pathway could be the following: human–cat–mouse–human [ 21 ]. Thus, an inter-species evolutionary trajectory for the Omicron outbreak is possible [ 20 , 21 ].…”
Section: Mutation Dynamic Is Associated With Omicron Evolutionmentioning
confidence: 99%
“…Considering the fact that the Omicron strain efficiently binds both the murine and the human ACE2-receptors, the possible evolution pathway could be the following: human–cat–mouse–human [ 21 ]. Thus, an inter-species evolutionary trajectory for the Omicron outbreak is possible [ 20 , 21 ]. In addition, immunocompromised HIV-infected patients could be favorable hosts for SARS-CoV-2 evolution [ 22 , 23 ].…”
Section: Mutation Dynamic Is Associated With Omicron Evolutionmentioning
confidence: 99%
“…It is known that the Omicron variant has a higher affinity for the ACE2 receptor and, consequentially, the potential for increased transmission [2]. The hACE2 receptor bound to the Omicron BA.2 spike trimer with a dissociation constant approximately 11-fold higher than that for the WT spike trimer and nearly 2-fold higher than that for the BA.1 spike trimer [29]. Among the Omicron sub-lineages, BA.2 and BA.3 have higher transmission potentials compared to BA.1: BA.2 has a docking energy of −974, which is higher than that of BA1.1 (−946.8) and BA.1 (−943.4) but lower than that of BA.3 (−999.3) [12].…”
Section: Increased Transmissibilitymentioning
confidence: 98%
“…Particularly, ACE2 has a 10-20-fold higher affinity to the Spike protein of SARS-CoV-2 than to that of SARS-CoV (Wrapp et al, 2020), which could suggest the severity of SARS-CoV-2-induced coronavirus disease 2019 (COVID-19). In addition, the recently prevalent SARS-CoV-2 mutant Omicron has produced much stronger infectivity, because the Spike trimer of Omicron (BA.2) exhibits 11-fold higher potency in binding to human ACE2 than that of the wild-type (WT) SARS-CoV-2 (Xu et al, 2022). Thus, ACE2 is the key target to control the infection of SARS-CoV-2 and even its current and future mutants.…”
Section: Introductionmentioning
confidence: 99%